Influence of Device Parameters on Performance of Ultra-Scaled Graphene Nanoribbon Field Effect Transistor. (7th December 2020) - Hasan, Md. Azizul; Nishat, Sadiq Shahriyar; Hossain, Mainul; Islam, Sharnali
Abstract : Recent advances in graphene nanoribbon (GNR) field-effect transistors (FETs), with finite band-gap, have shown great promise for their use in ultra-scaled, low power and high speed device applications. Here, we use quantum mechanical simulations, based on non-equilibrium Green's function (NEGF), to study the electrical characteristics of a sub-10 nm gate length GNRFET with double gate structure. Tight-binding approximation is used to extract the energy bands of GNR and the results are validated with density functional theory (DFT) calculations. Key electrical parameters are computed for different dielectric material, source/drain doping and temperature combining the channel length scaling beyond 10 nm to study performance variation. Results reveal that change in source/drain doping shows significant impact on performance for shorter channel, while the opposite tendency is observed for dielectric constant ( k) variation. GNRFET showed robustness against temperature variation compared to conventional Si devices. Finally, the results were benchmarked against the performance metrics of high performance and low power CMOS devices in the 5-nm technology node. A significant rise in leakage current beyond the LP requirement was observed for gate lengths below 5 nm. Results obtained from this study can provide useful insights in the design and implementation of next generation GNRFETs.